2014
DOI: 10.1177/0192623313516828
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Origin of Vildagliptin-induced Skin Effects in Cynomolgus Monkeys

Abstract: The purpose of this article is to characterize skin lesions in cynomolgus monkeys following vildagliptin (dipeptidyl peptidase-4 inhibitor) treatment. Oral vildagliptin administration caused dose-dependent and reversible blister formation, peeling and flaking skin, erosions, ulcerations, scabs, and sores involving the extremities at ≥5 mg/kg/day and necrosis of the tail and the pinnae at ≥80 mg/kg/day after 3 weeks of treatment. At the affected sites, the media and the endothelium of dermal arterioles showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Skin lesions in extremities of Cynomolgus monkeys were observed with vildagliptin during early pre-clinical studies at doses of ≥5 mg/kg/day. 4 The lesions were of vascular origin and were not observed in any other animal species. 4 Similarly, the vildagliptin pooled safety analysis did not find an increased incidence of all skin-related AEs with vildagliptin compared to comparators (1.6 versus 1.4/100 SYEs, respectively); however, data from the recently published signal detection studies using pharmacovigilance databases showed increased reports of bullous pemphigoid (BP) in patients using DPP-4 inhibitors.…”
Section: Adverse Events Of Special Interest For Patients With T2dmmentioning
confidence: 93%
See 2 more Smart Citations
“…Skin lesions in extremities of Cynomolgus monkeys were observed with vildagliptin during early pre-clinical studies at doses of ≥5 mg/kg/day. 4 The lesions were of vascular origin and were not observed in any other animal species. 4 Similarly, the vildagliptin pooled safety analysis did not find an increased incidence of all skin-related AEs with vildagliptin compared to comparators (1.6 versus 1.4/100 SYEs, respectively); however, data from the recently published signal detection studies using pharmacovigilance databases showed increased reports of bullous pemphigoid (BP) in patients using DPP-4 inhibitors.…”
Section: Adverse Events Of Special Interest For Patients With T2dmmentioning
confidence: 93%
“… 4 The lesions were of vascular origin and were not observed in any other animal species. 4 Similarly, the vildagliptin pooled safety analysis did not find an increased incidence of all skin-related AEs with vildagliptin compared to comparators (1.6 versus 1.4/100 SYEs, respectively); however, data from the recently published signal detection studies using pharmacovigilance databases showed increased reports of bullous pemphigoid (BP) in patients using DPP-4 inhibitors. 58 , 59 The majority of bullous skin lesions were observed in elderly patients, 60 which is consistent with the epidemiology data suggesting increasing age as a risk factor for BP 61 63 In accordance with the guidance on routine care, monitoring for skin lesions in patients with T2DM treated with a DPP-4 inhibitor is recommended.…”
Section: Adverse Events Of Special Interest For Patients With T2dmmentioning
confidence: 93%
See 1 more Smart Citation
“…These lesions were mediated by endothelial and medial hypertrophy/hyperplasia of arterioles at various levels of the dermis. These pathologic changes were related to increased NPY-Y 1 receptor signaling [33]. In humans, Boschmann et al showed that vildagliptin administration increased plasma norepinephrine (NE) concentrations in response to meals without causing a change in epinephrine levels [38].…”
Section: Cardiovascular Effects Of Dpp-4 Inhibitormentioning
confidence: 99%
“…In young infants or animals, placing the captor or maintaining it all throughout the experiment may turn out to be challenging if not impossible. In monkeys, recording HR either involves ECG or PPG under sedation [18][19][20] or implanting a telemetry device for HR measure during behaviour 21,22 . PPG recording or HR measures using captors embedded in a wearable jacket is also an option 11,23,24 .…”
mentioning
confidence: 99%